Proteinuria and Kidney Function Trajectories in Patients with Advanced CKD - Cheol Ho Park; Hyun Jun Hong; Hyung Woo Kim; Jung Tak Park; Tae Ik Chang; Tae-Hyun Yoo; Sue K. Park; Jung Soon Kim; Kyu-Beck Lee; Jong Cheol Jeong; Kook-Hwan Oh; Amanda H. Anderson; et al. (Clinical Journal of the American Society of Nephrology, 2026)
Introduction: While urine protein-to-creatinine ratio (UPCR) is more commonly used than urine albumin-to-creatinine ratio in routine care, and particularly in low-resource settings; its association with kidney function decline and projected time to reach a kidney failure estimated glomerular filtration rate (eGFR) threshold in advanced chronic kidney disease (CKD) remains underexplored. Methods: We analyzed 2,727 participants with eGFR 15–45mL/min/1.73 m 2 without kidney replacement therapy (KRT) from the Chronic Renal Insufficiency Cohort (CRIC) study and the KoreaN Cohort Study for Outcome in Patients with Chronic Kidney Disease (KNOW-CKD). The main exposures were baseline and time-updated UPCR. The primary outcome was CKD progression defined as 50% or more decline in eGFR from baseline measurement or the initiation of KRT. The secondary outcome was eGFR slope (mL/min/1.73 m 2 /year), whereas the exploratory outcome was projected time to reach the eGFR threshold of 10 mL/min/1.73 m 2 for kidney failure. Results: During 17,069 person-years of follow-up (median 4.9 years), the primary outcome occurred in 1,474 participants (54%). Compared with UPCR